HT process for treatment of PET fabrics with chitosan containing recipes - Mohammad Toufiqul Hoque; Kristina Klinkhammer; Boris Mahltig (Communications in Development and Assembling of Textile Products, 2023)
Polyester is the leading man-made fiber in the field of textiles and clothing. Polyester is usually dyed and finished using a process temperature in the range of 120 to 135 ºC. Such a process is known as a high-temperature (HT) process. The application of chitosan on cellulosic materials is an interesting approach to textile functionalization. In contrast, the application of chitosan by the HT process for the functional treatment of polyester is less investigated. With this background, the present study is related to the surface characteristics of different polyester fabrics with implemented chitosan after performing the HT process.